Hubungan Antara Faktor Usia dan Jenis Kelamin dengan Kejadian Demam Tifoid: Studi Klinis Di Yogyakarta - Ishak, Zulwina Ningsi; Irfani, Farida Noor; Bimantara, Arif (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Salmonella typhi is a bacterium that causes infection in the digestive tract known as typhoid fever. One of the diagnostic methods used to detect this disease is the Tubex test, which functions to identify the presence of antibodies. This study aims to determine the relationship between age and gender factors with the incidence of typhoid fever in one hospital in Yogyakarta during the period January-December 2024. This study used a descriptive design with a cross-sectional approach. A total of 127 samples were selected using the total sampling method with data obtained from medical records. Of these, (72.3%) were female patients and (27.7%) were male with the age group 20-39 years as the most frequently diagnosed group (62.7%). Bivariate analysis showed that the variables of age (p = 0.024 <0.05) and gender (p = 0.012 <0.05) had a significant relationship with the incidence of typhoid fever. Based on these results, there is a significant relationship between age and gender with the incidence of typhoid fever. Education regarding the implementation of a clean and healthy lifestyle needs to be increased, especially for women and productive age groups who are more vulnerable to typhoid infection.   Keywords: Typhoid Fever, Gender, Salmonella typhi, Age, Yogyakarta